The German-Polish „Potsdam” Border as Source of Imagination and Emotionalizing - JANIKOWSKI, Tobiasz (Transfer. Reception Studies, 2018)
The aim of this article is to outline the phenomenon of the Polish-German border in 1945 in the context of Imagination and Emotionalizing. Although the presentation platform – approximating the specificity of administrative-political lines separating Poland and Germany in the last century – introduces the recall of historical contexts, the primary tasks of the analyzes contain drawing conclusions from exploration, made in the area of broadly under-stood literature and journalism, showing the extent of the use of affective potentials related to the Polish-German border. In this context, it is impossible to resist the impression the current "Potsdam" border on the Odra and Nysa, clearly separate the state, national and ethnic structures of both countries, entailing a strong rooting in the collective identity of societies, moreover, becoming a field of diverse, often internally inconsistent, imaginations. A representative exemplification of this phenomenon are the literary, journalistic and scien-tific transformations of the described issues, invariably affecting the constitution and mod-eling the relations between Poland and Germany.